1974
DOI: 10.1016/0014-5793(74)80686-1
|View full text |Cite
|
Sign up to set email alerts
|

Active sites in Escherichia coli ribosomes

Abstract: The model of active sites in E. coli ribosome illustrated in the figure is based on the presently available experimental results. It is far from being complete and should not be overinterpreted as an accurate topographical model. More data on the functional role of ribosomal components and on the topography of the subunits can be expected in the near future and will add to the knowledge on the active sites in ribosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

1975
1975
1979
1979

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 117 publications
3
25
1
Order By: Relevance
“…We interprete this result that pyrophosphoryl transferase and elongation factor Tu can react simultanoulsy on the ribosomes, Our data indicate that the E. coli pyrophosphoryl transferase binds to a site different from that of the elongation factors. These findings are in good agreement with previous experiments in which it was shown that the two acidic proteins L7/L12 from the large ribosomal subunit are not required for the pyrophosphoryl transfer reaction [ 17,18], whereas they are for EF-Tu and EF-G functions [1,2]. The possibility that transferase and elongation factors do not bind to the same but rather to different ribosomes is unlikely, because ribosomes precharged with EF-Tu or EF-G were inactive in the pyrophosphoryl transferase-dependent formation of pppGpp and ppGpp but active in binding the transferase [16].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…We interprete this result that pyrophosphoryl transferase and elongation factor Tu can react simultanoulsy on the ribosomes, Our data indicate that the E. coli pyrophosphoryl transferase binds to a site different from that of the elongation factors. These findings are in good agreement with previous experiments in which it was shown that the two acidic proteins L7/L12 from the large ribosomal subunit are not required for the pyrophosphoryl transfer reaction [ 17,18], whereas they are for EF-Tu and EF-G functions [1,2]. The possibility that transferase and elongation factors do not bind to the same but rather to different ribosomes is unlikely, because ribosomes precharged with EF-Tu or EF-G were inactive in the pyrophosphoryl transferase-dependent formation of pppGpp and ppGpp but active in binding the transferase [16].…”
Section: Resultssupporting
confidence: 93%
“…It has been shown that the peptide chain elongation factor Tu (EF-Tu) and G (EF-G) from bacteria interact on ribosomes at a common region (for reviews see [1,2]). The existence of such a region has been demonstrated by competition experiments where ribosomes carrying EF-G are inactive in the EF-Tudependent Phe-tRNA binding reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates that all but S6 also bind directly to 16-S RNA when the latter is prepared by an acetic acid/urea method [lo]. Numerous investigations have demonstrated that the above proteins and others are important for initiationfactor-dependent binding of met-tRNA or EF-Tudependent binding of aminoacyl tRNA to the ribosome (see [27] and [50] for reviews). However, it should be borne in mind that the binding of tRNA in these experiments may be affected indirectly by such factors as the inhibition of mRNA or EF-Tu binding or subunit association.…”
Section: Ajjin Ity Chroma Togruphy ~F E Coli 30-s Ribosomal Proteinsmentioning
confidence: 99%
“…1970. as inactivation of ribosomal proteins or RNA by chemical modification [15-171, inhibition of a specific functional activity by reaction with antibodies directed against selected ribosomal proteins [ 18,191 and affinity labeling of ribosomal components physically situated at a specific binding site . A summary of some of this work is available [27]. From a correlation of these data one can infer that a surprisingly large number of ribosomal proteins from both subunits may be involved in interactions with extraribosomal RNA and protein factors during translation.…”
mentioning
confidence: 99%
“…In Escherichia coli, a protein in the large subunit of ribosome exists in both a-N-acetylated (L7) and unmodified (L12) forms [4,5]. This protein is involved in all the factor-dependent GTP hydrolysis steps carried out by the ribosome during protein biosynthesis (reviewed in [6]). …”
Section: Introductionmentioning
confidence: 99%